NEW KHALDUNISM IN THE THOUGHT OF ‘ABD AL-MAJĪD MIZIYĀN - Djebella Mohamed; Mokaddem Mokhtaria (International Journal of Innovative Technologies in Social Science, 2025)
This article examines the foundations of the “New Khaldunism” according to Dr. ‘Abd al-Majīd Miziyān. It aims to clarify his stance toward the inherited Khaldunian legacy and his vision for the methodology followed by social researchers—whom he regards as adherents of the New Khaldunism—should adopt when studying contemporary social phenomena, using the epistemological and methodological tools Ibn Khaldūn employed in his analysis of medieval Arab and Berber societies.